Upaya Pembentukan Karakter Anak melalui kajian rutin Kitab Ahlakul Banin Di Madrasah Diniyah Takmiliyah Ula Al-Muttaqin Jabung Mlarak Ponorogo - Fatakhul Huda Huda; Syahrudin (Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2024)
Abstrak This research aims to find out how to strengthen the values ​​of character education through learning the book Al-Akhlak Lil Banin at Madrasah Diniyah Takmiliyah Ula Al-Muttaqin Jabung Mlarak Ponorogo. This research is descriptive field research with a qualitative approach. Data collection techniques through observation, interviews and documentation. The data analysis technique is as proposed by Miles and Huberman, through data reduction, data display, and data verification. From this research, it can be found that efforts to strengthen the value of character education through learning the book Al-Akhlak Lil Banin at Madrasah Diniyah Takmiliyah Ula Al-Muttaqin Jabung Mlarak Ponorogo are: religious values, discipline values, love of cleanliness, and family values. Madrasah Diniyah Takmiliyah Ula Al-Muttaqin Jabung Mlarak Ponorogo uses several methods including, methods of understanding, habituation, role modeling or example, and requires students to obey all existing regulations in the Madrasah (reward and punishment). Where the four values ​​of character education contained in the book Al-Akhlak Lil Banin and the method of instilling character education have been implemented quite well and more planting has begun to strengthen the value of character education for students.